Light-driven water oxidation using hybrid photosensitizer-decorated Co3O4 nanoparticles. (September 2018) - De Tovar, Jonathan; Romero, Nuria; Denisov, Sergey A.; Bofill, Roger; Gimbert-Suriñach, Carolina; Ciuculescu-Pradines, Diana; Drouet, Samuel; Llobet, Antoni; Lecante, Pierre; Colliere, Vincent; Freixa, Zoraida; McClenaghan, Nathan; et al.
Abstract: Cobalt nanoparticles (NPs) have been prepared by hydrogenation of the organometallic complex [Co(η 3 -C8 H13 )(η 4 -C8 H12 )] in 1-heptanol in the absence of any other stabilizer and then transformed into Co3 O4 NPs using mild oxidative reaction conditions. After deposition onto glassy carbon rotating disk electrodes, the electrocatalytic performance of the Co3 O4 NPs in water oxidation has been tested in 1M NaOH. The activity has been benchmarked with that of state-of-the-art Co3 O4 NPs through electrochemically-active surface area (ECSA) and specific current density measurements. Furthermore, the covalent grafting of photosensitive polypyridyl-based Ru II complexes onto the surface of Co3 O4 NPs afforded hybrid nanostructured materials able to photo-oxidize water into O2, while steady-state and time-resolved spectroscopic measurements gave some further insight into kinetics and pertinent reaction steps following excitation. These first-row transition metal oxide hybrid nanocatalysts display better catalytic performance than simple mixtures of non-grafted photosensitizers and Co3 O4 NPs, thus evidencing the advantage of the direct coupling between the two entities for the photo-induced water oxidation reaction. Graphical abstract: Photo-induced water oxidation catalysis with hydrid Ru-photosensitizer-Co3 O4 nanoparticles is described. Covalent grafting of Ru-based photosensitizers to Co3 O4 nanoparticles leads to 1 st -row transition-metal based oxygen evolving hybrid dyads showing advanced photocatalytic performance with regards to simple mixtures of their unbound components. Image 1 Highlights: Co and Co3 O4 nanoparticles have been synthesized by the organometallic approach. The electrocatalytic water oxidation activity of the Co3 O4 nanoparticles has been assessed. Ru-polypyridyl photosensitive complexes have been covalently grafted onto the Co3 O4 nanoparticles. The hybrid Ru-photosensitizer-Co3 O4 nanoparticles are able to photocatalytically oxidize water with higher performance than the mixtures of the unbound components.